'Cukup for me to be successful in this country': 'staying' among left‐behind young women in Indonesia's migrant‐sending villages. (29th April 2019) - SOMAIAH, BITTIANDRA CHAND; YEOH, BRENDA S. A.; ARLINI, SILVIA MILA
Abstract: By examining the aspirations of young, rural Indonesian women who, unlike their parents, want to stay behind rather than migrate for work, we look at how these women's experiences of feeling left‐behind affect their quests for alternative futures. Using a household relational lens, we employ the mediating concept of enough ( cukup ) to analyse the aspirations of young women wishing to remain at home. By focusing on their commitment to inter‐generational continuity and care rather than a lack of choice, we are able to offset the discourses associated with the culture of migration and its accompanying remittance euphoria. Our findings showed three main reasons for their choice. First, these young women pursue remittance‐funded higher education as a counter to parental sacrifice. Second, staying allows them both to provide the hands‐on care they themselves were denied as children and to pursue meaningful local careers. Third, the idea that migration has been 'enough' is a rational response to the social risks with which migration confronts a family.